2022
DOI: 10.1007/s00586-022-07359-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement rates, adverse events and predictors of clinical outcome following surgery for degenerative cervical myelopathy

Abstract: Purpose To investigate improvement rates, adverse events and predictors of clinical outcome after laminectomy alone (LAM) or laminectomy with instrumented fusion (LAM + F) for degenerative cervical myelopathy (DCM). Methods This is a post hoc analysis of a previously published DCM cohort. Improvement rates for European myelopathy score (EMS) and Neck Disability Index (NDI) at 2- and 5-year follow-ups and adverse events are presented descriptively for avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The potential benefits must be weighed against the risk of complications with spinal surgery. One prospective registry study identified a 15% incidence of adverse events in the first year following surgery ( de Dios et al, 2022 ). In our clinical experience, not all patients with mild DCM opt for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The potential benefits must be weighed against the risk of complications with spinal surgery. One prospective registry study identified a 15% incidence of adverse events in the first year following surgery ( de Dios et al, 2022 ). In our clinical experience, not all patients with mild DCM opt for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The time from onset of symptoms to diagnosis was significantly greater in DCM. Delayed diagnosis is a recognised problem in DCM that results in treatment delays [1,33]; this is particularly problematic given the fact that the best response to surgery may be seen after early intervention [34]. This observation does not preclude a similar problem of delayed and missed diagnoses in DTM.…”
Section: Discussionmentioning
confidence: 99%
“…T he available medical literature has shown that surgical procedures can improve functional status and quality of life by relieving spinal cord compression, especially in multilevel degenerative cervical myelopathy (MDCM). [1][2][3][4][5][6][7][8][9] Currently, anterior cervical spinal fusion surgery including anterior cervical discectomy fusion (ACDF) and anterior cervical corpectomy fusion (ACCF) are routinely used in patients with MDCM. Although ACDF can alleviate the compression by removing the disc and osteophyte directly.…”
Section: Introductionmentioning
confidence: 99%